2015
DOI: 10.1161/circheartfailure.114.001244
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Endoplasmic Reticulum Stress–Mediated C/EBP Homologous Protein Activation in Coxsackievirus B3–Induced Acute Viral Myocarditis

Abstract: Background— This study tested the hypothesis whether endoplasmic reticulum (ER) stress/C/EBP homologous protein (CHOP) signaling is linked with coxsackievirus B3 (CVB3)–induced acute viral myocarditis (AVMC) in vivo. Methods and Results— AVMC was induced by intraperitoneal injection of 1000 tissue culture infectious dose (TCID 50 ) of CVB3 virus in mice. In AVMC mouse hearts (n=11), ER stress and CHOP were sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 47 publications
0
28
0
Order By: Relevance
“…ER stress-related caspase 12 and CHOP proteins participate in apoptosis regulation (Kamarehei et al 2019 ). It has been shown that the activation of PERK-eIF2α-ATF4 pathway results in increased CHOP expression that up-regulates Bax/Bcl-2 ratio and finally causes caspase-3 activation (Cai et al 2015 ). Previous research indicated that the activation of ER-specific caspase-12 can trigger the following activation of caspase-9 and caspase-3, which leads to an apoptotic caspase cascade (Kim et al 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…ER stress-related caspase 12 and CHOP proteins participate in apoptosis regulation (Kamarehei et al 2019 ). It has been shown that the activation of PERK-eIF2α-ATF4 pathway results in increased CHOP expression that up-regulates Bax/Bcl-2 ratio and finally causes caspase-3 activation (Cai et al 2015 ). Previous research indicated that the activation of ER-specific caspase-12 can trigger the following activation of caspase-9 and caspase-3, which leads to an apoptotic caspase cascade (Kim et al 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…CVs are responsible for a broad range of diseases that can be life-threatening in children and neonates; however, little is known about their induced pathogenicity and how they interact with the human gut epithelium, their primary site of infection. While animal models have been used to study the biology and pathogenesis of CV infection [ 24 , 25 ], current murine models largely rely on inoculation into the intraperitoneal space or directly into the brain, and thus, they fail to recapitulate the natural route of infection through the respiratory and intestinal mucosa [ 26 28 ]. Recently, a 3D culture model that recapitulates shear stress in the intestine by culturing Caco2 cells on extracellular matrix-coated beads in a rotating wall vessel bioreactor was used to study CVB3 infection [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cardiomyocyte cellular damage may be induced by infection with pathogens, endogenous stress from mechanical or oxidative traumas, or from mutated proteins ( Figure 1A-C) [19][20][21][22]. These insults promote activation of the innate immune response through pattern recognition receptors (PRRs), such as Toll-like receptors (TLRs) and Nod-like receptors (NLRs).…”
Section: Development Of Cardiac Autoimmunitymentioning
confidence: 99%